2018
DOI: 10.1002/hbm.24433
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different cerebrospinal fluid and white matter fMRI filtering strategies—Quantifying noise removal and neural signal preservation

Abstract: This study examines the impact of using different cerebrospinal fluid (CSF) and white matter (WM) nuisance signals for data‐driven filtering of functional magnetic resonance imaging (fMRI) data as a cleanup method before analyzing intrinsic brain fluctuations. The routinely used temporal signal‐to‐noise ratio metric is inappropriate for assessing fMRI filtering suitability, as it evaluates only the reduction of data variability and does not assess the preservation of signals of interest. We defined a new metri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…We found that the tSNR difference between RETROICOR without WM/CSF regression (Figure 3, the top row) and RETROICOR with WM/CSF regression (Figure 3, the 2nd row) was relatively minor, suggesting that WM/CSF regression and RETORICOR can be used together without inflating the noise. These results were consistent with previous studies 37,40 using both WM/CSF regression and RETROICOR to suppress the physiological noise.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the tSNR difference between RETROICOR without WM/CSF regression (Figure 3, the top row) and RETROICOR with WM/CSF regression (Figure 3, the 2nd row) was relatively minor, suggesting that WM/CSF regression and RETORICOR can be used together without inflating the noise. These results were consistent with previous studies 37,40 using both WM/CSF regression and RETROICOR to suppress the physiological noise.…”
Section: Discussionsupporting
confidence: 93%
“…Several recent papers that used white matter as a nuisance regressor even cited literature supporting the existence of physiological signals in white matter, but then proceeded regardless of this evidence, offering little in the form of counterargument. For example, Bartoň et al (2019) acknowledged the existence of fMRI detectable white matter activation, but then continued to use white matter signals as a nuisance regressor, with no justification or rationale. Similarly, Yang et al (2019) acknowledged some of the white matter activation literature, but then also disregarded it, citing the “lack of neurons in white matter,” a statement that is clearly anatomically incorrect (Kukley et al, 2007; García-Marín et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These bundles may convey information related to execution and goal-directed tasks ( 77 79 ). Although the white matter BOLD signal was considered as a nuisance signal that was usually regressed out from the dataset during the preprocessing ( 80 ), several studies have reported the white matter fMRI-BOLD signal and disregarded its previous categorization as a blind spot in the functional imaging ( 81 85 ). Our robust white matter EEG-fMRI associations with the reduced HRF peak and the amplified HRF trough corroborate this recent blind spot hypothesis.…”
Section: Discussionmentioning
confidence: 99%